Diagnosis dan Tatalaksana Tromboemboli pada Kehamilan - Muhammad Perdana Airlangga (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2017)
Venous thromboembolism is both more common and more complex to diagnose in patients who are pregnant than in those who are not pregnant. Pulmonary embolism and deep-vein thrombosis are the two components of a single disease called venous thromboembolism. Pulmonary embolism is the leading cause of maternal death in the developed world. Delayed diagnosis, delayed or inadequate treatment, and inadequate thromboprophylaxis account for many of the deaths due to venous thromboembolism. Successful strategies for the management of venous thromboembolism in nonpregnant patients have been established. However, many of the recommendations for the treatment of pregnant patients who have venous thromboembolism are not based on high-quality data; rather, they are derived from observational studies and extrapolation from studies involving nonpregnant patients. The purpose of this review is to provide a practical approach to the diagnosis, management, and prevention of venous thromboembolism in pregnant patients.